Age-structured population growth rates in constant and variable environments: a near equilibrium approach - Dewi, S.; Chesson, P. (2004)
General measures summarizing the shapes of mortality and fecundity schedules are proposed. These measures are derived from moments of probability distribution related to mortality and fecundity schedules. Like moments, these measures form infinite sequences, but the first terms of these sequences are of particular value in approximating the long term-faster growth rate of an age structured population that is growing slowly. Higher order terms are needed for approximating faster growing populations. These approximations offer a general nonparametric approach to the study of life-history evolution in both constant and variable environments. These techniques provide simple quantitative representations of the classical findings that, with fixed expected lifetime and net reproductive rate, type I mortality and early peak reproduction increase in the absolute magnitude of the population growth rate, while type III mortality and delayed peak reproduction reduce this absolute magnitude.